2018
DOI: 10.2319/042318-311.1
|View full text |Cite
|
Sign up to set email alerts
|

Contact of the incisive canal and upper central incisors causing root resorption after retraction with orthodontic mini-implants: A CBCT study

Abstract: Objectives: To explore risk factors for contact between the incisive canal (IC) and upper central incisors (U1) and to evaluate the relationship between contact and root resorption using cone-beam computer tomography (CBCT). Materials and Methods: This retrospective study used CBCT data of 33 patients treated by a senior orthodontist. Anterior teeth were retracted with mini-implants, and CBCT scans were taken before and after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 18 publications
(28 reference statements)
2
48
0
Order By: Relevance
“…It is assumed that the size and configuration of the incisive canal contributes to root resorption. This notion is further supported by the fact that the difference in the amount of resorption between roots contacting the incisive canal and those without contact in a previous study 21 was similar to the difference between the left and right central incisors in the present case (Table 2). Previously, Cho et al 6 reported that the incisive canal width is larger than the inter-root distance in over 60% patients.…”
Section: And Thesupporting
confidence: 89%
“…It is assumed that the size and configuration of the incisive canal contributes to root resorption. This notion is further supported by the fact that the difference in the amount of resorption between roots contacting the incisive canal and those without contact in a previous study 21 was similar to the difference between the left and right central incisors in the present case (Table 2). Previously, Cho et al 6 reported that the incisive canal width is larger than the inter-root distance in over 60% patients.…”
Section: And Thesupporting
confidence: 89%
“…In 2-dimensional cephalometric radiograph, Björk et al 22 24 have established superimposition based on stable regions using metallic implants. Since its introduction in 1980s 25 , CBCT has proved to be an efficient tool in detecting problems of craniofacial structures and made it possible to superimpose on three-dimensional structures 3 , 4 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, insufficiency of the maxillary width during tooth movement could be a risk associated with root resorption [28]. One study observed the relationship between contact the incisive canal of upper central incisors and root resorption [29]. The results showed that contact between upper incisors and the cortical plate of the incisive canal cause significantly more apical root resorption.…”
Section: Discussionmentioning
confidence: 99%